2007
DOI: 10.1007/s11255-007-9268-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression: Does it have a probable role in tumorigenesis mechanisms of renal cell carcinoma?

Abstract: Although COX-2 expression is not an independent predictor of progression in patients with RCC, patients with higher ISS values have significantly shorter progression-free survival rates. These results might be important to the clinician because positive COX-2 expression of a certain RCC might necessitate early adjuvant systemic therapy to delay the progression of RCC. For this reason, there is a need for innovative, prospective, and randomized studies in patients with positive COX-2 expression that will displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Indeed, we were able to detect a similar connection between HuR and COX-2 expression in the RCC cell line, since HuR knockdown by siRNA led to the reduced expression of COX-2. The expression of COX-2 was shown to be associated with an advanced stage of RCC and other clinicopathological features such as tumour size and grade, but it is not an independent prognostic factor in RCC [15,[23][24][25]. Our results are in line with these previous results, as here COX-2 expression was associated with high nuclear grade and high clinical stage.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, we were able to detect a similar connection between HuR and COX-2 expression in the RCC cell line, since HuR knockdown by siRNA led to the reduced expression of COX-2. The expression of COX-2 was shown to be associated with an advanced stage of RCC and other clinicopathological features such as tumour size and grade, but it is not an independent prognostic factor in RCC [15,[23][24][25]. Our results are in line with these previous results, as here COX-2 expression was associated with high nuclear grade and high clinical stage.…”
Section: Discussionsupporting
confidence: 90%
“…COX-2 expression has also been reported to correlate with cRCC prognosis. Although the precise relationship is not well-understood, most published studies report COX-2 expression to correlate with poor clinicopathologic features and predict a poor prognosis (Miyata et al , 2003; Tuna et al , 2004; Sozen et al , 2008; Li et al , 2009). One report, however, found that COX-2 expression predicted for a longer median overall survival (Kankuri-Tammilehto et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They inhibit tumor growth by inducing apoptosis of tumor cells and inhibiting the Wnt/␤-catenin signaling pathway [34]. In RCC, COX-2 expression is present in the majority of the tumors and correlates with worse stage, grade, and microvessel density and poorer survival [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%